ANALISA DAYA DUKUNG TANAH DASAR DAN PERKERASAN LANDASAN PACU DENGAN ADANYA PENINGKATAN KAPASITAS PELAYANAN PESAWAT (STUDI KASUS BANDAR UDARA TANJUNG WARUKIN KALIMANTAN SELATAN) - Legeno Joko Pratomo; Lucky Amperawan Schipper (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2020)
Potential aircraft service improvement at Warukin Airport Tabalong Regency of SouthKalimantan assuming the increase of passengers whose destination of departure and returnis equated with the activities of the airport in South Kalimantan province. Improvement of airportaircraft service with type planning – the runway type with various methods, methods and typesof machining is recommended according to the most possible criteria to be implemented. Thecarrying capacity of the existing base soil and the existing layer of pavement is analyzed for the needsof analysis method of the runway determination.